Diversification in banking is noninterest income the answer? - Kevin J. Stiroh (Federal Reserve Bank of New York, 2002)
The U.S. banking industry is steadily increasing its reliance on nontraditional business activities that generate fee income, trading revenue, and other types of noninterest income. This paper assesses potential diversification benefits from this shift. At the aggregate level, declining volatility of net operating revenue reflects reduced volatility of net interest income, rather than diversification benefits from noninterest income, which is quite volatile and has become more correlated with net interest income. At the bank level, growth rates of net interest income and noninterest income have also become more correlated in recent years. Finally, greater reliance on noninterest income, particularly trading revenue, is associated with higher risk and lower risk-adjusted profits. These results suggest little obvious diversification benefit from the ongoing shift toward noninterest income.
Keywords: 330; Bank; Diversifikation; Einnahmen; Gewinn; USA